The impact of hydro-electric development to water resource in Tay Nguyen area - Dân, Nguyễn Lập; Long, Ngô Lê; An, Ngô Lê; Huy, Dương Quốc; Thi, Chu Bá (Vietnam Journal of Earth Sciences, 2014)
Tay Nguyen area (Highland) is considered to be the original water resource of most of the rivers flowing into the East Sea in the coastal Middle area, South East (Vietnam) and area of two provinces named Rotanak Kiri and Mondul Kiri (Cambodia). Due to favorable terrain, Highland posesses relatively abundant hydro-electric energy for Vietnamese central region. Hydro-electric reservoirs have been contributing significantly to the sustainable development of socioeconomy and environment, security and national defense in the area. However, the considerable development of hydroelectric power in the Highland has been assessed in different perspectives in society. This article deeply analyses the impacts of hydro-electricity to water resource in the Highland and proposes solutions to the problems such as the establishment of River Basin Commission and Review hydro-electric Planning to serve multiple purposes in the major river systems in Tay Nguyen area.